The Malay Translation Of The Qur'an: An Evaluation Based On Scientific Exegesis - Ahmad Bazli Bin Ahmad Hilmi; Selamat Amir; Mohd Yakub @ Zulkifli Mohd Yusoff; Monika @ Munirah Abd Razzak; Ahmad Farid Ibrahim (Universiti Malaya, 2024)
Jurnal Usuluddin (Januari – Jun 2014) 39:111-133